DAMPAK KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENANGGULANGAN KEMISKINAN DI KABUPATEN BANJAR TAHUN 2013 – 2018 - Muhammad Rizaldy Nugraha; Nasruddin Nasruddin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Muhammad Rizaldy Nugraha (2019), The Impact of Family Hope Program Policies in Poverty Alleviation in the Banjar District in 2013-2018.This study aims to (1) Know the implementation of the Family Hope Program (PKH) in Banjar District. (2) Determine the impact of the Family Hope Program (PKH) policy on poverty reduction in Banjar District.The respondents in this study were 99 respondents from Banjar district, and the method used in data processing was the data tabulation method, and descriptive qualitative.The results of this study indicate that the policy impact of the Family Hope Program in Poverty Reduction in Banjar District has a positive impact on poverty reduction. PKH policy provides short-term and long-term benefits, in the short term the Family Hope Program policy provides assistance to KSM (Very Poor Families) / RTSM (Very Poor Households) to meet their daily needs. And for the long term the Family Hope program provides a variety of trainings that will become provisions for them in the future.Keywords : Poverty Alleviation, Family Hope Program, Very Poor Family / Very Poor Households